2008
DOI: 10.1007/s11240-008-9430-9
|View full text |Cite
|
Sign up to set email alerts
|

Histological study of somatic embryogenesis induction on zygotic embryos of macaw palm (Acrocomia aculeata (Jacq.) Lodd. ex Martius)

Abstract: The aim of this paper was to describe the histological events that led to somatic embryogenesis in macaw palm (Acrocomia aculeata (Jacq.) Lodd. ex Martius). Zygotic embryos were inoculated on Y 3 medium containing 9 lM 4-amino-3,5,6-trichloropicolonic acid (picloram). Somatic embryos regenerated from nodular callus on induction medium with activated charcoal under photoperiod or without activated charcoal under dark. Many proembryos originated from the fundamental meristem after 10-20 days of culture. When tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
23
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 34 publications
10
23
0
4
Order By: Relevance
“…In multicellular origin, somatic embryos are histologically fused with the mother tissue and could also fuse with other somatic embryos (Moura et al 2008). This process of origin was most frequent in A. aculeata, but these embryos did not regenerate plants (Moura et al 2008). In the present study, somatic embryos showed the same multicellular origin, which could explain the low conversion rate.…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…In multicellular origin, somatic embryos are histologically fused with the mother tissue and could also fuse with other somatic embryos (Moura et al 2008). This process of origin was most frequent in A. aculeata, but these embryos did not regenerate plants (Moura et al 2008). In the present study, somatic embryos showed the same multicellular origin, which could explain the low conversion rate.…”
Section: Discussionsupporting
confidence: 43%
“…In zygotic embryos, somatic embryos formed close to procambial strands of calli and had two origins: unicellular and multicellular. In multicellular origin, somatic embryos are histologically fused with the mother tissue and could also fuse with other somatic embryos (Moura et al 2008). This process of origin was most frequent in A. aculeata, but these embryos did not regenerate plants (Moura et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…During the indirect somatic embryogenesis different types of callus are frequently produced, some of which have potential to generate plants. Identification of callus cells with embryogenic potential can be achieved through cytological and ultrastructural analysis (Fillipi et al 2001, Steiner et al 2005, Moura et al 2008, thereby greatly enhancing the efficiency of the in vitro propagation process.…”
Section: Introductionmentioning
confidence: 99%
“…Propagation is usually carried out through seeds, but the development and improvement of in vitro propagation techniques are necessary to speed up and facilitate genetic breeding programs. Somatic embryos in vitro were recently obtained (Moura et al, 2008(Moura et al, , 2009, but the rate of plantlets conversion is still low.…”
Section: Introductionmentioning
confidence: 99%